Not Only About Price but Also Lifestyle: Recent Phenomena of Backpacker Umrah In Indonesia - Pitaya, Pitaya; Makhasi, Ghifari Yuristiadhi Masyhari; Hanafiah‬, Mohd Hafiz (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Abstract: The increasing interest of the Indonesian Muslim community to perform umrah has been previously studied by many researchers. However, the phenomenon of backpacker umrah, which has attracted the middle-class Muslim community in Indonesia in the last decade, has not been widely discussed. Backpacker umrah is different from conventional umrah because it does not get complete facilities from travel agencies, so the price is lower. This study explores the motivation of umrah pilgrims to choose backpacker umrah solely because of lower prices or other considerations. Then how far is the response of umrah travel agents to this new trend? This type of research is qualitative research that uses a phenomenological approach. The method used was the observation, questionnaires, and unstructured interviews with 15 backpacker umrah participants determined by a snowball. The results of this study indicate that there are other motivations besides low prices, namely lifestyle. In addition, the selection of the type of umrah that is not tied to a schedule can be more solemn in worship. Although it does not publish directly as one of its products, the umrah travel agency responds to this backpacker umrah phenomenon by seeing it as an economic opportunity by providing land arrangement facilities.Abstrak: Meningkatnya minat masyarakat muslim Indonesia untuk melakukan umrah sudah banyak dikaji oleh peneliti. Namun fenomena umroh backpacker yang menarik minat masyarakat muslim kelas menengah di Indonesia dalam satu dekade terakhir ini belum banyak didiskusikan. Umroh backpacker berbeda dengan umroh konvensional karena tidak mendapatkan fasilitas yang lengkap dari biro perjalanan sehingga harganya lebih murah. Penelitian ini menggali motivasi jemaah umrah memilih backpacker umrah semata-mata karena harga yang lebih murah atau pertimbangan lain. Lalu sejauh mana respon travel agent umrah terhadap tren baru ini? Jenis penelitian ini adalah penelitian kualitatif yang menggunakan pendekatan fenomenologis. Metode yang digunakan adalah observasi, angket, dan wawancara tidak terstruktur dengan 15 peserta umroh backpacker yang ditentukan dengan bola salju. Hasil enelitian ini menunjukkan bahwa ada motivasi lain selain harga yang murah yaitu gaya hidup. Selain itu, pemilihan jenis umroh yang tidak terikat jadwal bisa lebih khusyuk dalam beribadah. Meski tidak mempublikasikan secara langsung sebagai salah satu produknya, biro perjalanan umrah merespon fenomena umrah backpacker ini dengan melihat sebagai peluang ekonomi dengan memberikan fasilitas land arrangement.